2012
DOI: 10.1039/c2cc31606d
|View full text |Cite
|
Sign up to set email alerts
|

Fluoranthene based fluorescent chemosensors for detection of explosive nitroaromatics

Abstract: A novel fluoranthene based fluorescent chemosensor for the detection of picric acid (PA) at the parts per billion (ppb) level was evaluated. Static fluorescence quenching was the dominant process by intercalative π-π interaction between fluoranthene (S(1)) and nitroaromatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
129
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(131 citation statements)
references
References 27 publications
1
129
1
Order By: Relevance
“…In 2012, Patil and co-workers reported two π-electron-rich fluoranthene based fluorescence sensors 41 and 42 for trace and selective detection of NACs at 15 ppb level of concentration (Chart 7). 48,49 Compound 41 was synthesized by Knoevenagel condensation between 1,3-bis(4bromophenyl)propan-2-one and acenapthenedione, 48 while 42 was obtained by three-step synthetic process employing 1,2bis[4-(hydroxyl)phenyl]ethyne and 7,9-bis-(4-bromophenyl)-8H-20 cyclopenta [a]acenaphthylen-8-one in ethanol medium. [48][49] The presence of -Br atoms and unsymmetrical phenyl moiety in 41 effectively helped the self-association via π─π interactions and formed 1D-supramolecular arrangement in solid-state through layer-by-layer self-assembly, while solid-state packing of 42 25 revealed a Z-shaped supramolecular arrangements stabilized by strong C-H…π interactions.…”
Section: Fluoranthene Based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Patil and co-workers reported two π-electron-rich fluoranthene based fluorescence sensors 41 and 42 for trace and selective detection of NACs at 15 ppb level of concentration (Chart 7). 48,49 Compound 41 was synthesized by Knoevenagel condensation between 1,3-bis(4bromophenyl)propan-2-one and acenapthenedione, 48 while 42 was obtained by three-step synthetic process employing 1,2bis[4-(hydroxyl)phenyl]ethyne and 7,9-bis-(4-bromophenyl)-8H-20 cyclopenta [a]acenaphthylen-8-one in ethanol medium. [48][49] The presence of -Br atoms and unsymmetrical phenyl moiety in 41 effectively helped the self-association via π─π interactions and formed 1D-supramolecular arrangement in solid-state through layer-by-layer self-assembly, while solid-state packing of 42 25 revealed a Z-shaped supramolecular arrangements stabilized by strong C-H…π interactions.…”
Section: Fluoranthene Based Sensorsmentioning
confidence: 99%
“…48,49 Compound 41 was synthesized by Knoevenagel condensation between 1,3-bis(4bromophenyl)propan-2-one and acenapthenedione, 48 while 42 was obtained by three-step synthetic process employing 1,2bis[4-(hydroxyl)phenyl]ethyne and 7,9-bis-(4-bromophenyl)-8H-20 cyclopenta [a]acenaphthylen-8-one in ethanol medium. [48][49] The presence of -Br atoms and unsymmetrical phenyl moiety in 41 effectively helped the self-association via π─π interactions and formed 1D-supramolecular arrangement in solid-state through layer-by-layer self-assembly, while solid-state packing of 42 25 revealed a Z-shaped supramolecular arrangements stabilized by strong C-H…π interactions. The difference in structural arrangements and intrinsic micro-porosity envisaged that both 41 and 42 could be potential sensors that intercalate the electrondeficient NACs via π−π interactions and thus exert an efficient The obtained linear SV plot and invariant fluorescence lifetime with increasing the concentration of PA suggested that observed fluorescence quenching follows static mechanism through ground-state donoracceptor complex formation.…”
Section: Fluoranthene Based Sensorsmentioning
confidence: 99%
“…To date, various fluorescent chemo-sensors [4][5][6], conjugated polymers [7][8][9][10], fluorescent nanofibres [11][12][13], and nanoparticles [14,15] have been reported as being able to detect nitro derivatives [16][17][18][19]. However, the majority of the reports lacks high selectivity, which is needed for the practical use of PA sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The most common explosives appear to be presented by the class of nitroaromatic compounds (NACs), which have received a great attention during the last decades due to global terror threats, and also because of their high toxicity for the environment [8][9][10][11][12]. A variety of analytical methods have been developed for sensitive detection of nitroaromatic compounds [7].…”
Section: Introductionmentioning
confidence: 99%